Beyond the digital divide: Towards a situated approach to open data. (13th July 2017) - Bezuidenhout, Louise M.; Leonelli, Sabina; Kelly, Ann H.; Rappert, Brian
Abstract: Poor provision of information and communication technologies in low/middle-income countries represents a concern for promoting open data. This is often framed as a 'digital divide' and addressed through initiatives that increase the availability of information and communication technologies to researchers based in low-resourced environments, as well as the amount of resources freely accessible online. Using qualitative empirical data from a study of lab-based research in Africa we highlight the limitations of this framing and emphasize the range of additional factors necessary to effectively utilize data available online. We adapt Sen's 'capabilities approach' to highlight the distinction between simply making resources available, and fostering researchers' ability to use them. This provides an alternative orientation that highlights the persistence of deep inequalities within the seemingly egalitarian-inspired open data landscape. We propose that the extent and manner of future data sharing will hinge on the ability to respond to the heterogeneity of research environments.